Optimization of instant corn cream soup formulation containing chicken bone and moringa leaf using linear programming - Rike Tri Kumala Dewi; Ihsan Iswaldi; Kevin Basakara Jaya; Wafa Armitha Kwando; Rebecca Clarissa; Alwin Winardi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Chicken bone and moringa leaf can be used as raw materials in food products because of their high protein, calcium, and phosphorus content. This study aimed to identify the optimal formulation for producing instant corn cream soup with added chicken bones and moringa leaf meal, having a high protein, calcium, and phosphorus content with minimal raw material costs. The formulation was developed using a randomized group design with a combination of chicken bone (0%, 1.4%, 2.8%) and moringa leaf (0%, 1.1%, 2.2%). Then, the formulation was analyzed using linear programming with constraints based on SNI 01-4967-1999 regarding instant cream soup and PerBPOM No. 1 of 2022 regarding the supervision of claims on labels and advertisements of processed food. The three best formulas were subjected to a sensory test. The results showed that three of the nine formulas had the highest protein, calcium, and phosphorus content with the lowest raw material cost, i.e., Formula 5 (2.8% chicken bone, without moringa leaf), Formula 7 (2.8% chicken bone and 1.1% moringa leaf), and Formula 9 (2.8% chicken bone and 2.2% moringa leaf). These formulations also met the requirement for high calcium and high phosphorus in accordance with PerBPOM No. 1 of 2022. However, the samples did not reach the minimum requirement to be considered high protein. The sensory test results showed that Formula 7 was the closest to the ideal product and was also preferred by respondents.